Effects of soy protein to wheat gluten ratio on the physicochemical properties of extruded meat analogues. (January 2019) - Chiang, Jie Hong; Loveday, Simon M.; Hardacre, Allan K.; Parker, Michael E.
Graphical abstract: Highlights: 30%WG showed highest degree of texturisation, hardness and chewiness. 30%WG exhibited fibrous structures interconnected with much smaller fibres. A large portion of protein in meat analogues was linked with hydrogen bonds. Disulphide bonds play a role in fibrous structure formation in meat analogues. Abstract: This study reported on the effects of soy protein concentrate (SPC) to wheat gluten (WG) ratio at a constant mass of SPC and WG on the physicochemical properties of extruded meat analogues. Meat analogues (∼57% moisture content) were extruded at maximum barrel temperature of 170 °C, at a dry and water feed rate of 2.8 kg/h and 3.6 kg/h, respectively. The physical, chemical and textural properties of meat analogues were studied, where meat analogues containing 30%WG showed the highest degree of texturisation, fibrous structure, hardness and chewiness using instrumental and sensory analysis. Layered or fibrous microstructure of meat analogues was observed using scanning electron microscopy and light microscopy. Meat analogues containing 20%WG and 30%WG were found to exhibit fibrous microstructure with large fibrous structures interconnected with much smaller fibres. The types of chemical bonding in meat analogues were tested with urea (U), dithiothreitol (DTT) and sodium dodecyl sulphate (SDS); findings suggested that a large portion of aggregated proteins were linked with hydrogen bonds. Disulphide bonds became increasingly important as the amount of WG was increased, and synergies between hydrogen bonds and disulphide bonds were evident from increased solubility effects with mixed solvents, especially U and DTT. It was concluded that processing conditions during extrusion denatured the proteins, allowing increased crosslinking, which facilitated the formation of fibrous structures.